Genome of Pythium myriotylum Uncovers an Extensive Arsenal of Virulence-Related Genes among the Broad-Host-Range Necrotrophic Pythium Plant Pathogens - Paul Daly; Dongmei Zhou; Danyu Shen; Yifan Chen; Taiqiang Xue; Siqiao Chen; Qimeng Zhang; Jinfeng Zhang; Jamie McGowan; Feng Cai; Guan Pang; Nan Wang; et al. (Microbiology Spectrum, 2022)
ABSTRACT The Pythium (Peronosporales, Oomycota) genus includes devastating plant pathogens that cause widespread diseases and severe crop losses. Here, we have uncovered a far greater arsenal of virulence factor-related genes in the necrotrophic Pythium myriotylum than in other Pythium plant pathogens. The genome of a plant-virulent P. myriotylum strain (~70 Mb and 19,878 genes) isolated from a diseased rhizome of ginger (Zingiber officinale) encodes the largest repertoire of putative effectors, proteases, and plant cell wall-degrading enzymes (PCWDEs) among the studied species. P. myriotylum has twice as many predicted secreted proteins than any other Pythium plant pathogen. Arrays of tandem duplications appear to be a key factor of the enrichment of the virulence factor-related genes in P. myriotylum. The transcriptomic analysis performed on two P. myriotylum isolates infecting ginger leaves showed that proteases were a major part of the upregulated genes along with PCWDEs, Nep1-like proteins (NLPs), and elicitin-like proteins. A subset of P. myriotylum NLPs were analyzed and found to have necrosis-inducing ability from agroinfiltration of tobacco (Nicotiana benthamiana) leaves. One of the heterologously produced infection-upregulated putative cutinases found in a tandem array showed esterase activity with preferences for longer-chain-length substrates and neutral to alkaline pH levels. Our results allow the development of science-based targets for the management of P. myriotylum-caused disease, as insights from the genome and transcriptome show that gene expansion of virulence factor-related genes play a bigger role in the plant parasitism of Pythium spp. than previously thought. IMPORTANCE Pythium species are oomycetes, an evolutionarily distinct group of filamentous fungus-like stramenopiles. The Pythium genus includes several pathogens of important crop species, e.g., the spice ginger. Analysis of our genome from the plant pathogen Pythium myriotylum uncovered a far larger arsenal of virulence factor-related genes than found in other Pythium plant pathogens, and these genes contribute to the infection of the plant host. The increase in the number of virulence factor-related genes appears to have occurred through the mechanism of tandem gene duplication events. Genes from particular virulence factor-related categories that were increased in number and switched on during infection of ginger leaves had their activities tested. These genes have toxic activities toward plant cells or activities to hydrolyze polymeric components of the plant. The research suggests targets to better manage diseases caused by P. myriotylum and prompts renewed attention to the genomics of Pythium plant pathogens.